The Effect of Palm Fibers on Concrete Compressive Strength - Mukhlis, Mukhlis; Mirani, Zulfira; Lusyana, Lusyana; Safira, Adinda; Fawzar, Rifqie Adityo (JURUSAN TEKNIK SIPIL, 2023)
Due to its superior compressive strength, concrete is a building material that is frequently employed in construction.. The development of technology and infrastructure requires the development of concrete technology to improve concrete performance. Utilizing fiber-reinforced concrete is one method of enhancing concrete's characteristics. Concrete and fiber, both synthetic and natural, are combined to create fiber-reinforced concrete. Palm fiber is one type of natural fiber that can be used as fiber in concrete. This experiment aims to ascertain the impact of palm fiber addition on the compressive strength of concrete. Three cylindrical examples, each measuring 300 mm in height and 150 mm in diameter, were constructed. In this study, the variations are addition of palm fiber of 0%, 1.5%, 2.5%, and 3% of cement weight. The test findings demonstrated that at concrete ages of 14 days and 28 days, adding 1.5% produced the maximum compressive strength of concrete. The 28-day average compressive strength of fine aggregate concrete (gradation Ⅳ) is 68.83% higher than that of ordinary concrete. Coarse-grained and fine-grained aggregate concrete (gradation II) has an average life expectancy of 28 days, and its compressive strength is 57.1% higher than that of ordinary concrete.